Uncovering Language Learning Beliefs Behind Novice Arabic Learners' Accelerative Speaking Success: A BALLI Analysis in a Pesantren Higher Education - Evi Khulwati; Arini El Haq; Nurmia Nasution; Suci Ramadhona; Intan Syarifah Nur (CV Edujavare Publishing, 2026)
This study maps the language learning beliefs profile of novice learners who successfully mastered speaking skills at the Muslim Cendekia Institute (IMC). Using an explanatory case study approach, data were gathered through BALLI questionnaires from 64 new female students, oral exam scores, and in-depth interviews with 9 informants. The questionnaire analysis shows that the students' language belief scores fall into the high category (3.91–4.68). This aligns with oral exam documents confirming mass success, where 71.9% of the students achieved high performance at the end of the semester. The key factors for this accelerative success include: 1) Incubation Period (Silent Period): The language-free policy during the first two months effectively reduced affective filters. This policy shifted rigid perfectionism into a risk-taking strategy. 2) Spiritual Motivation: The integration of spiritual-theocentric motivation achieved the highest score (4.82). This value transformed the mandatory language regulation in the third month into a religious moral need rather than an institutional burden. This study implies the importance of providing a language regulation grace period and addressing internal affective factors for novice learners in a full immersion environment.